The Role of Civic Spirituality in Strengthening Socio-Cultural Values to Support SDGs in Education - Sukron Mazid; Novitasari Novitasari; Achmad Busrotun Nufus; Delfiyan Widiyanto; Ni’matu Sholikhah (IAIN Madura, 2026)
This study examines the role of civic spirituality in strengthening socio-cultural values to support Sustainable Development Goals (SDGs) implementation in education. Using a qualitative field study approach, data were collected through observation, in-depth interviews with teachers and students, and documentation of learning activities. Findings indicate that civic spiritual values integrated into learning activities and school culture effectively strengthen socio-cultural values including mutual cooperation, tolerance, discipline, and responsibility. This integration is realized through habituation activities, subject integration, and cultural practices supporting character formation. Civic spirituality also enhances student awareness of diversity, social responsibility, and global citizenship, aligning with SDGs principles of quality and inclusive education. Success factors include active teacher involvement, a conducive school environment, and relevant local cultural support. The study recommends systematic integration of civic spirituality into curricula and educational practices to advance SDGs achievement, positioning it as a strategic approach beyond cognitive learning toward sustainable character development.